INDONESIAN TRANSLATION ANALYSIS OF DESCRIPTIVE ADJECTIVES IN APPLE PRODUCTS’ SLOGANS - Raden Roro Shinta Felisia (Jurnal Sosial Humaniora dan Pendidikan, 2023)
Apple, a technological company based in California, has one official Indonesian website. This website contains Indonesian product slogans translated from the English website. Since it conveys a product quality, a descriptive adjective is a language component frequently used in an Apple product slogan. This study aims to describe the Indonesian translation of descriptive adjectives in Apple products’ slogans. The result is two (2) translations referring to the literal translation strategy, one (1) referring to the free translation strategy, and one (1) referring to the creative translation strategy. As a brand component, a slogan and its translation are important in the development of a brand identity.